2004
DOI: 10.1007/s10350-003-0037-2
|View full text |Cite
|
Sign up to set email alerts
|

Limberg Flap Repair for Pilonidal Sinus Disease

Abstract: The Limberg flap procedure is an easy and effective technique. Patient comfort, quick healing time, early return to full activity, and low complication and recurrence rates are the important advantages of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 19 publications
3
55
1
6
Order By: Relevance
“…In the literature, the rate of wound-related complications (such as infection, seroma, hematoma, dehiscence or necrosis) after LFR varies from 4.7 to 15.9% [10,13]. The complication rates rise to 15.9% in small series and fall as low as 4.7% in large series [5,[10][11][12][13][14]. The higher complication and recurrence rates in the present study may be attributed to our limited experiences on LFR for sacrococcygeal PD.…”
Section: Discussioncontrasting
confidence: 67%
“…In the literature, the rate of wound-related complications (such as infection, seroma, hematoma, dehiscence or necrosis) after LFR varies from 4.7 to 15.9% [10,13]. The complication rates rise to 15.9% in small series and fall as low as 4.7% in large series [5,[10][11][12][13][14]. The higher complication and recurrence rates in the present study may be attributed to our limited experiences on LFR for sacrococcygeal PD.…”
Section: Discussioncontrasting
confidence: 67%
“…[18] Daphan et al operated on 147 patients with a median follow-up time of 13.1 months, and recurrence was noted 4.8%. [21] In our study, we operated on 353 patients, and recurrence was found to be 3.1%.…”
Section: Discussionmentioning
confidence: 92%
“…The length of the hospital stay for the different techniques have been reported 29 days for incision and drainage [17], 10 to 21 days for the excision-open-packing technique [15]. The operated number of patients and length of hospital stay by Topgül et al [18], Erdem et al [19], Eryilmaz et al [20], and Daphan et al [21] was 200 patients, 3.1 days; 40 patients, 3.5±1.16 days; 63 patients, 3 days; 147 patients, 5.9 days, respectively. In our study, we operated on 353 patients, and the mean length hospital stay was 4.51± 2.85 days.…”
Section: Discussionmentioning
confidence: 96%
“…[5][6][7][8] With flap surgery, the resulting defective area after wide excision is filled with well-vascularized fasciocutaneous tissue and its superiority to primary closure and marsupialization has been reported in many articles. [9][10][11][12] An important point in pilonidal sinus surgery is that the sacral region has a flat anatomic plane; in contrast, the intergluteal region has a sulcus overlying the coccyx that curves toward anus. The medial parts of the buttocks deepen down to this sulcus.…”
mentioning
confidence: 97%